Curcumin as a Therapeutic Agent in Dementia: A Mini Systematic Review of Human Studies - Natascia Brondino; Simona Re; Annalisa Boldrini; Antonella Cuccomarino; Niccolò Lanati; Francesco Barale; Pierluigi Politi (The Scientific World Journal)
Dementia is a leading health problem worldwide, with Alzheimer’s disease (AD) representing up to 60% of all dementia cases. A growing interest has recently risen on the potential use of natural molecules in this condition. Curcumin is a polyphenolic compound traditionally used in Indian medicine. Several in vitro and in vivo studies have found a protective effect of curcumin in AD. In the present systematic review we aimed to evaluate the state-of-the-art of clinical trials of curcumin in AD. We retrieved three published studies, while there are several ongoing clinical trials. To date there is insufficient evidence to suggest the use of curcumin in dementia patients. Of note, short-term use of curcumin appears to be safe. Several reasons could be responsible for the discrepancy between in vitro and in vivo findings and human trials, such as low bioavailability and poor study design.